Teachers’ Assessment of Inattentive Classroom Behavior Among Primary School Students in Ilorin City, Kwara State, Nigeria - Ajiboye, Samuel Kolawole; Adebayo, David Obafemi; Abubakar, Saidu (Universitas Pendidikan Indonesia, 2020)
Inattentive behavior could become unnoticed but it is often a major constraint to effective classroom instruction and students’ performance. This research investigated teachers’ assessment of inattentive classroom behavior among primary school students in Ilorin city, Kwara State, Nigeria. The research is a survey research with the population consisted of 1,568 teachers, while 160 participants were purposively selected. A questionnaire type of instrument was used in the research. The results showed a reliability coefficient of r = 0.81 after conducting the test-retest reliability. The research question was analyzed with descriptive statistics while the hypotheses were tested with t-test and ANOVA at the 0.05 level of significance. Inattentive classroom behavior was high among primary school students as assessed by teachers. Teachers’ assessment of students’ inattentive behavior was similarly based on gender and qualification but different based on work experience. It was recommended that early childhood education/primary school teachers and counselors as well as other stakeholders in primary education should synergize to mitigate the high level of inattentive classroom behavior among students in order to enhance teaching-learning.